Experimental and Numerical Studies of the Seismic Performance of Precast Segmental Concrete Columns - Li, Chao (Curtin University, 2019)
Precast segmental concrete column has many advantages, but its applications are limited due to insufficient knowledge about its seismic performance. This thesis aims to investigate the seismic performance of precast segmental column. Cyclic tests and shake table tests were carried out to evaluate the static and dynamic performance of the precast segmental column. Extensive numerical studies were also conducted as supplementary to the experimental results for better understanding of its seismic performance.